Linguistic Contributions to the Development of Translation Studies in China - Luo, Xuanmin (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1999)
AbstractThis paper tries to draw a clear picture of linguistic contributions to the development of translation in China. It does so by means of a bilateral study focusing on the development of the unit of language and translation. Works of Chinese translation theorists are cited to illustrate different efforts in applying linguistic theory to translation studies, among which the textual approach is cardinal.